Customer review on Kinrara Resort, Selangor through booking.com and Agoda / Edina Abd Rahman and Nurannisa Syifa Abd Shukor - Abd Rahman, Edina; Abd Shukor, Nurannisa Syifa (Faculty of Hotel and Tourism, Universiti Teknologi MARA, 2018)
This study investigated the customer review in Kinrara Resort by using Booking.com and Agoda. An observation has been conduct to collect data through Online Travel Agency (OTA). The choose of sample which is Kinrara Resort is due to the less study that has been conduct before specifically about the result. The objective of this study to understand the customer reviews on several factors on Kinrara Resort by using Booking.com and Agoda. Moreover, this study also wants to understand the effect of customer review reflected towards the resort through resort's booking. The factors that have been used for frequency analysis is cleanliness, comfort, location, facilities, staff and value for money. This study will be used the qualitative research design by using secondary data as the research instrument. The result shows that most factors that have a highest rating is the location for both Booking.com and Agoda. While the lowest rating that customer choose is the service.